2016
DOI: 10.1186/s40854-016-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance and capital structure of IPOs in Pakistan from 2000 to 2015

Abstract: Background: When a privately owned firm or privatized government entity raises capital by selling its stocks for the first time to general public, is known as initial public offering (IPO). The underpricing phenomenon and ownership structure are important characteristics of IPO process that significantly affect the short-run and long-run performance of private firm and privitized entity. This study compares the short-and long-run performance, and factors affecting these performances for both private IPOs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…For instance, there is a negative correlation with oversubscription in Pakistan (Mehmood et al, 2020), yet a positive one in Greece (Kenourgios et al, 2007). Mixed results are reported by other studies (Dhamija and Arora, 2017;Hearn, 2014;Javid and Malik, 2016;Omran, 2005;Sahoo and Rajib, 2010;Tran et al, 2013). Regarding information determinants, studies document a positive correlation with the media tone of conveying information in China (Zhang et al, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 87%
“…For instance, there is a negative correlation with oversubscription in Pakistan (Mehmood et al, 2020), yet a positive one in Greece (Kenourgios et al, 2007). Mixed results are reported by other studies (Dhamija and Arora, 2017;Hearn, 2014;Javid and Malik, 2016;Omran, 2005;Sahoo and Rajib, 2010;Tran et al, 2013). Regarding information determinants, studies document a positive correlation with the media tone of conveying information in China (Zhang et al, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 87%
“…In Pakistan's IPO market, IPO issuers are avoiding the risk of losing money on the table, where the issuance of IPOs has decreased continuously. Previous literature examined the initial return phenomena and demonstrated that ex ante uncertainty, market capitalization, information asymmetry, corporate governance, market sentiment, ownership structure, issue size, aftermarket IPOs risk, issue timings, market volatility, pricing mechanism, premium and underwriter reputation are factors that significantly influence initial return (Afza et al, 2013;Aslam and Ullah, 2017;Javid and Malik, 2016;Kayani and Amjad, 2011;Khalid and Raheman, 2009;Mumtaz et al, 2016;Sohail et al, 2018b;Zubair and Ahmed, 2014;Mehmood et al, 2020c).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the context of Pakistan, past studies concerning initial return issues reported a range of significant determinants, such as offer size and price, firm size, ownership structure, information asymmetry, ex-anti-certainty, market sentiment, aftermarket risk, subscription ratio, size of private firm and government entity, issue timing, and underwriter reputation, market volatility, market capitalisation (Aslam & Ullah, 2017;Javid & Malik, 2016;Kayani & Amjad, 2011;Khalid & Nasr, 2007;Sohail, Bilal, Rukh, & Fatima, 2018b). The Pakistan's security market size, regulatory framework, institutional setting, and efficiency of market differ from those of other developing nations.…”
Section: Introductionmentioning
confidence: 99%